Magnetic Microbubbles Combined with ICG-Loaded Liposomes for Synergistic Mild-Photothermal and Ferroptosis-Enhanced Photodynamic Therapy of Melanoma - Xiong K; Luo G; Zeng W; Wen G; Wang C; Ding A; Qi M; Liu Y; Zhang J (International Journal of Nanomedicine)
Kaifen Xiong,1,2 Guanghong Luo,3 Wei Zeng,4 Guanxi Wen,4 Chong Wang,1,5,6 Aijia Ding,1,2 Min Qi,7 Yingying Liu,4 Jianglin Zhang1,5,6 1Department of Dermatology, Shenzhen People’s Hospital, The second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China; 2Department of Dermatology, Xiangya Hospital, Central South University, Changsha, Hunan, People’s Republic of China; 3Department of Radiation Oncology, Shenzhen People’s Hospital, The second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China; 4Department of Ultrasonography, Shenzhen People’s Hospital, second Clinical Medical College of Jinan University, First Clinical Medical College of Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China; 5Candidate Branch of National Clinical Research Center for Skin Diseases, Shenzhen, Guangdong, People’s Republic of China; 6Department of Geriatrics, Shenzhen People’s Hospital, The second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, Guangdong, People’s Republic of China; 7Department of Plastic Surgery, Shenzhen Hospital, Southern Medical University, Shenzhen, People’s Republic of ChinaCorrespondence: Yingying Liu; Jianglin Zhang, Email yingyingliu@ext.jnu.edu.cn; zhang.jianglin@szhospital.comBackground: Melanoma poses a significant threat to human health due to the lack of effective treatment options. Previous studies have demonstrated that the combination of photothermal therapy (PTT) and photodynamic therapy (PDT) can enhance therapeutic efficacy. However, conventional PTT/PDT combination strategies face various challenges, including complex preparation processes, potential damage to healthy tissues, and insufficient generation of reactive oxygen species (ROS). This study aims to design a rational and efficient PTT/PDT therapeutic strategy for melanoma and to explore its underlying mechanisms.Methods: We first synthesized two target materials, indocyanine green-targeted liposomes (ICG-Lips) and magnetic microbubbles (MMBs), using the thin-film hydration method, followed by characterization and performance evaluation of both materials. Subsequently, we evaluated the synergistic therapeutic effects and underlying mechanisms of ICG-Lips combined with MMBs in melanoma treatment through in vitro experiments using cellular models and in vivo experiments using animal models.Results: Herein, we developed a multifunctional system comprising ICG-Lips and MMBs. ICG-Lips enhance targeted delivery through specific binding to the S100B protein on melanoma cells, while MMBs, via ultrasound (US)-induced cavitation effects, shorten the uptake time of ICG-Lips by melanoma cells and improve uptake efficiency. Furthermore, the combination of ICG-Lips and MMBs induces significant reactive oxygen species (ROS) generation. Under 808 nm laser irradiation, the accumulation of ICG-Lips in melanoma cells achieves mild photothermal therapy (mPTT) and PDT effects. The elevated temperature and excessive ROS generated during these processes result in glutathione (GSH) depletion, ultimately triggering ferroptosis. The occurrence of ferroptosis further amplifies PDT efficacy, creating a synergistic effect that effectively suppresses melanoma growth. Additionally, the combined therapeutic strategy of ICG-Lips and MMBs demonstrates excellent biosafety.Conclusion: In summary, this study presents a novel and straightforward strategy that integrates mPTT, PDT, and ferroptosis synergistically to combat melanoma, thereby laying a solid foundation for improving melanoma treatment outcomes.Keywords: magnetic microbubbles, ferroptosis, mild-temperature photothermal therapy, photodynamic therapy, synergistic therapy